2017
DOI: 10.1212/nxg.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of age at onset variation in spinocerebellar ataxia type 2

Abstract: Objective:To examine heritability of the residual variability of spinocerebellar ataxia type 2 (SCA2) age at onset (AO) after controlling for CAG repeat length.Methods:From 1955 to 2001, dates of birth, CAG repeat lengths, AO, sex, familial inheritances, and clinical manifestations were collected for a large Cuban SCA2 cohort of 382 affected individuals, including 129 parent-child pairs and 69 sibships. Analyses were performed with log-transformed AO in the GENMOD procedure to predict AO using repeat length, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…This is particularly well illustrated for the CAG/polyglutamine diseases, nine disorders in which relatively modest CAG repeat expansions encode abnormally long stretches of glutamine in the respective disease proteins. In all nine CAG/polyglutamine diseases, there is a strong inverse correlation between repeat length and age of symptom onset: longer repeats cause earlier disease that usually has more profound signs and symptoms (3,36,40,59,62,66,70,75,108,115,122,126,129). The size of the expanded CAG repeat is itself the key determinant for age of onset, accounting for 45% to 70% of the effect, depending on the specific disease.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly well illustrated for the CAG/polyglutamine diseases, nine disorders in which relatively modest CAG repeat expansions encode abnormally long stretches of glutamine in the respective disease proteins. In all nine CAG/polyglutamine diseases, there is a strong inverse correlation between repeat length and age of symptom onset: longer repeats cause earlier disease that usually has more profound signs and symptoms (3,36,40,59,62,66,70,75,108,115,122,126,129). The size of the expanded CAG repeat is itself the key determinant for age of onset, accounting for 45% to 70% of the effect, depending on the specific disease.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship varies between diseases and the difference in age at onset is not accounted for solely by the TNR repeat length. A substantial portion of this residual variance is heritable [3,24].…”
Section: Autosomal Dominant Cerebellar Ataxiamentioning
confidence: 99%
“…The length of TNR expansion above the disease threshold is inversely proportional to the age of onset [22,23]. A substantial portion of this residual variance is heritable [3,24]. A substantial portion of this residual variance is heritable [3,24].…”
Section: Introductionmentioning
confidence: 99%
“…Once the length of the CAG repeat has been accounted for, the residual AOO variance can be considered as a heritable trait, implying the existence of genetic modifiers. 51,52 A recent study identified non-pathological repeat lengths in other CAG-containing disease loci, that act in trans with wildtype alleles (SCA1, SCA6, SCA7), as modifiers of disease onset in 1255 patients from the EUROSCA cohort. 53 These findings were partly replicated by other studies in smaller cohorts.…”
Section: Modifiers Of Aoomentioning
confidence: 99%